2020
DOI: 10.1111/gcbb.12692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several establishment modes of Miscanthus × giganteus and Miscanthus sinensis on yields and yield trends

Abstract: Miscanthus is a C4 perennial grass originating from East Asia, the yields of which progressively increase in the first years of growth. Several species for bioenergy have been studied since the mid‐1980s in Europe, in particular (Miscanthus × giganteus [M. × giganteus]), due to its high yields. M. × giganteus is mainly cultivated in France and established from rhizomes. Our study aimed to assess, in field conditions, alternative establishment methods combined with an alternative species, Miscanthus sinensis (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…(2015) showed that after 14 years of cultivation, the quantity of mulch (crop residues present on the soil surface, originating from fallen leaves and harvest losses) was similar under M. × giganteus (9.3 t/ha of DM) and M. sinensis (8.9 t/ha of DM). Furthermore, the leaf area index was also similar for both genotypes in our trial network, despite lower yields for M. sinensis than for M. × giganteus (Ouattara et al., 2020). We can therefore assume that the aboveground C inputs were similar between the two genotypes.…”
Section: Discussionsupporting
confidence: 60%
“…(2015) showed that after 14 years of cultivation, the quantity of mulch (crop residues present on the soil surface, originating from fallen leaves and harvest losses) was similar under M. × giganteus (9.3 t/ha of DM) and M. sinensis (8.9 t/ha of DM). Furthermore, the leaf area index was also similar for both genotypes in our trial network, despite lower yields for M. sinensis than for M. × giganteus (Ouattara et al., 2020). We can therefore assume that the aboveground C inputs were similar between the two genotypes.…”
Section: Discussionsupporting
confidence: 60%
“…During the juvenile phase of miscanthus cultivation, yields increase before reaching a plateau [5,10,31,32]. The effect of crop age on yield is more pronounced for M. x giganteus than M. sinensis because of its longer juvenile period [5]. Moreover, the higher the previous year's yields, the higher the current year's yields, at least for the juvenile phase.…”
Section: Site-years Is Partially Common For M X Giganteus and M Sinensismentioning
confidence: 99%
“…x giganteus and M. sinensis. During the juvenile phase of miscanthus cultivation, yields increase before reaching a plateau [5,10,31,32]. The effect of crop age on yield is more pronounced for M. x giganteus than M. sinensis because of its longer juvenile period [5].…”
Section: Site-years Is Partially Common For M X Giganteus and M Sinensismentioning
confidence: 99%
See 2 more Smart Citations